POLITIK SELEBRITI: PERLAWANAN TERHADAP SISTEM (STUDI KASUS GAYA KOMUNIKASI POLITIK PADA KANDIDAT PRESIDEN UKRAINA VOLODYMYR ZELENSKY) - Andika Hendra Mustaqim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This study aims to examine in depth about celebrity politics as part of political communication by Ukrainian presidential candidate Volodymyr Zelenskiy who won the election in 2019 in two rounds. The paradigm of this research is critical constructivist with the case study research method based on Zelensky's speeches and political statements in the mass media. The results of the analysis and discussion showed that Zelensky's popular celebrity status was Zelensky's main selling power and strengthened his position, used a political communication style approach that opposed mass media hegemony, maximized the role of social media, did not attend talk shows, and did not attend public debates. It shows the offer of an approach that actually challenges the system neatly and constructively, but destructively. However, the various policy programs offered by Zelensky actually did not dare to fight the mainstream, they still followed the flow, such as supporting EU and NATO membership, fighting Russia, and strengthening the Ukrainian economy. A popular policy that is different from Zelensky is its efforts to legalize marijuana, prostitution and gambling in certain cities.